Advancements in Medical Textiles and the Integration of Herbal Extracts (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Medical textiles, also known as healthcare textiles, are a rapidly advancing segment of technical textiles with applications in wound care, infection control, tissue engineering, and medical devices. Current research focuses on developing multifunctional textiles that enhance safety, therapeutic performance, and environmental sustainability while minimizing cross-infection risks in healthcare settings. In this context, the incorporation of herbal bioactives has gained attention due to their inherent antimicrobial, anti-inflammatory, antioxidant, and wound-healing properties. Extracts derived from medicinal plants such as Azadirachta indica (neem), Aloe vera, Curcuma longa (turmeric), and Ocimum sanctum (tulsi) offer natural, biocompatible, and biodegradable alternatives to conventional synthetic finishes used in medical textiles. The intention of this review article is to critically examine recent developments in medical textiles, with a specific emphasis on the medical classification, requirements, and performance of healthcare textiles. It covers various techniques involved in the finishing of fabrics with herbal extracts, such as coating, grafting, microencapsulation, sol-gel processing, and nanotechnology-assisted delivery systems. This review presents future opportunities for herbal-functionalized medical textiles as sustainable and patient-centric solutions for next-generation healthcare applications.